Counselling Cancer Patients: A Case Study of Perspectives of Professional Counsellors and Cancer Patients in Malaysia - Siok Ping, Voon; Siaw Leng, Chan (Human Resource Management Academic Research Society, 2021)
Globally, cancer is renowned as the top leading cause of death. Given the severity of this illness, cancer patients often experience different problems ranging from psychological adjustment and physiological changes to a financial burden. Counselling cancer patients is one treatment option provided to provide support and constructive coping of uncertain outcomes. The present case study aimed to explore the counsellors' perspectives in counselling with cancer patients and cancer patients' views in counselling. This research study utilised a qualitative case study design to investigate the patients' and counsellors' perspectives in-depth. A professional counsellor who has experience in counselling cancer patients and cancer patients was recruited to learn about central importance issues in this study. Six themes have emerged from the research: (1) opinion about cancer, (2) opinion regarding counselling with cancer patients in Malaysia, (3) problems and concerns surround cancer patients, (4) difficulties and challenges working with cancer patients, (5) needs of the terminally ill, and (6) strategies and recommendations in counselling cancer patients. The finding provides professional counsellors with some indications in working together with cancer patients and terminally ill patients, which can be a complex and challenging process